(untitled) (Research, Society and Development, 2021)
Diabetes mellitus is a predisposing factor for dermatomycosis, despite it is not yet completely understood, especially in regards to those living in rural areas. Objective: To evaluate the occurrence of dermatomycosis in diabetics, aged over 60 years old, living in the rural area of Ivatuba, Paraná, Brazil. Methods: Patients of HiperDia program answered a questionnaire and provided blood samples, and cutaneous lesions scraped, for laboratory investigation. Results: forty-five individuals were included in the study, of which 37 had cutaneous lesions and were investigated in the laboratory. Fungi were detected in 17 of them (45.9%), with dermatophytes being the most frequent agents. There was no significant difference in the assessed metabolic parameters of individuals with and without mycosis, nor in terms of rural life habits, however some fungi sampled were resistant to phagocytosis and especially to death by phagocytes from diabetic animals. Conclusion: A high rate of dermatomycosis was detected in individuals with diabetes, probably related to the failure in the activation of phagocytes.